Comparative assessment of cardiovascular risk in European and Korean ethnic groups in the Russian population using the SCORE and SCORE2 - D. Yu. Bogdanov; V. A. Nevzorova; E. Yu. Shestopalov (Кардиоваскулярная терапия и профилактика)
Aim. To carry out a comparative assessment of cardiovascular risk (CVR) in people aged 40-49 years of European and Korean ethnicity with a single residence area using the Systematic Coronary Risk Evaluation (SCORE) and SCORE2 scales.Material and methods. We examined 397 and 50 apparently healthy individuals of the European (EEG) and Korean (KEG) ethnic groups, respectively, who were evaluated for CVR according to the SCORE and SCORE2 charts.Results. According to the SCORE system, the median CVR in the EEG was 0 [0-0] vs 0 [0-1]% in the KEG (p<0,001), while from a clinical point of view, the groups did not differ from each other. The SCORE2 system demonstrated more significant clinical results as follows: the median risk in EEG individuals was 5 [3-8]%, which corresponds to a high CVR for this age group, and 8 [4-11]% in KEG individuals, which corresponds to a very high CVR (p=0,011). CVR assessment in apparently healthy individuals is decisive in considering the preventive measures. According to the SCORE system, 97,5% and 96% of apparently healthy EEG and KEG individuals, respectively, are classified as low and moderate risk. High and very high risk when using this system was determined in 2,5 and 4% among Europeans and Koreans, respectively. However, using the SCORE2 system, only 10,3% of Europeans were classified as low/ moderate risk, and among ethnic Koreans — 8%. At the same time, the category of high and very high risk was designated, respectively, for 63,7 and 25,9% in the EEG and 40 and 52% in the KEG, respectively. It has been established that according to the SCORE2 system, more than half of Koreans aged 40-49 already have a very high CVR, which significantly distinguishes this group from the European population.Conclusion. The SCORE2 system has a more differentiated approach in determining individual CVR. The SCORE2 assessment of non-high density lipoprotein cholesterol levels makes it more personalized for use in different ethnic populations.